Localization of Exogenous Mesenchymal Stem Cells in a Pig Model of Lung Transplantation - Piatkowski, Tanja; Brandenberger, Christina; Rahmanian, Parwis; Choi, Yeong-Hoon; Zeriouh, Mohamed; Sabashnikov, Anton; Wittwer, Thorsten; Wahlers, Thorsten C. W.; Ochs, Matthias; Mühlfeld, Christian (The Thoracic and Cardiovascular Surgeon, 2018)
Background Mesenchymal stem cells (MSCs) have a great potential for the treatment of acute lung injury. This study provides a detailed immunohistochemical and stereological analysis of the localization and distribution of exogenous MSC in a pig model of lung transplantation after intravascular or endobronchial application.Methods MSC derived from human bone marrow were labeled by DiI and administered intravascularly or endobronchially to the lungs of donor pigs after a period of 3 hours warm and 3 hours cold ischemia. The left lung was transplanted to a recipient pig and reperfused for 4 hours before fixation. The right donor lung was fixed for microscopic analysis directly after the ischemia time.Results After both administration routes, a similar number of exogenous MSC was found in the lungs. Within each animal, the heterogeneity of MSC distribution was high both with respect to left and right lung as well as to the different lobes of each lung. After endobronchial application, MSC were found in alveolar and bronchial/bronchiolar lumen, whereas after intravascular administration, they were mainly observed in blood vessels.Conclusion Although the administration of exogenous MSC is possible by endobronchial or intravascular application, it yields a heterogeneous distribution in the lungs which may warrant strategies to improve a more homogeneous distribution.
Keywords: lung transplantation; stem cells; cell culture